Cervical cancer screening trials in India and ethical issues - Labani, Satyanarayana; Asthana, Smita (Indian Journal of Community Health, 2014)
Cervical cancer is a preventable disease with an annual global load of 528000 new cases and 266000 deaths, majority occurring in low resource countries (LRCs). The magnitude of the disease in India is with 123000 new cases and 67000 deaths every year [1]. Developing countries successfully implemented Pap smear based cervical cancer screening into public health services and achieved reduction in incidence and mortality. With lack of the infrastructural resource requirements and trained technical manpower, LRCs including India do not have current capacity to implement cytology based Pap screening. Several alternatives to Pap testing were extensively studied in observational study settings. Visual inspection with acetic acid (VIA) is considered to be effective alternative method to reduce the disease burden in LRCs. Studies are conducted in randomized trial settings to confirm whether a significant reduction in incidence and mortality can be achieved in a real programme settings.